Molecular Pathways in Cancers - Cristóbal, Ion; Rodríguez, Marta (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book includes some recent works providing the readers with novel relevant findings about the main signaling pathways that govern the molecular pathogenesis of some of the highest prevalent human tumors, which are the basis for developing alternative therapeutic strategies to improve patient outcomes.